New North American Records of Aquatic Insects as Paratenic Hosts of Pheromermis (Nematoda: Mermithidae) - D. P. Molloy; Vinikour, W. S.; Anderson, R. V. (Journal of Invertebrate Pathology, 1999)
Several species of aquatic insects in Trout Park Nature Preserve (Elgin, IL) were observed to have small, black spots (<0.1 mm diameter) visible within their bodies. Microscopic examination revealed these spots to be coiled juveniles of a mermithid (Nematoda: Mermithidae). Based on host habitat (seepage areas and rivulets), host species (aquatic insects), and size (mean diameter of coiled juveniles = 79 μm), it is likely that these mermithids were in the genus Pheromermis. Since adult mermithids were not found, species determination was not feasible, and the possibility of a new species cannot be ruled out. Pheromermis pachysoma and Pheromermis vesparum, however, are two species known to use aquatic insects as paratenic (i.e., transport) hosts in order to reach their definitive hosts, vespid wasps. Wasp larvae are infected by consuming the flesh of adult aquatic insects that contain the coiled juveniles of these Pheromermis spp. Of the 19 macroinvertebrate species examined in this study, Pheromermis juveniles were found in 4 caddisfly species (Hesperophylax designatus, Lepidostoma liba, Glossosoma intermedium, and Diplectrona modesta) and in 2 stonefly species (Clioperla clio and Amphinemura delosa). In addition to all 6 insect species being new host records for Pheromermis infection, this also represents the first report of nematode infection in stoneflies within the Western Hemisphere and of a Pheromermis sp. in Illinois. Among trophic groups, insect detritivores have been frequently recorded infected with coiled Pheromermis juveniles because of their direct consumption of eggs, and we also observed this for detritivores in our investigation (e.g., L. liba and A. delosa). Because C. clio was intensively infected, however, our study also provided evidence that predatory insects can be paratenic hosts. Coiled juveniles were typically present in muscle and fat body and present in almost all body regions. Not every infected paratenic host had external signs of infection; thus, dissections are required for accurate determination of infection prevalence and intensity. Our findings, in conjunction with those made in previous studies, indicate that a wide variety of aquatic insects may be used as paratenic hosts by Pheromermis. Because of their small size, it is highly likely that coiled juveniles are either overlooked or mistaken for melanized integumental wounds during field studies of aquatic insects. A more careful inspection for these coiled juveniles in aquatic insects, especially detritivores and their predators in seepage areas, would probably reveal that Pheromermis is far more common than presently documented.
Keywords: Amphinemura delosa; Clioperla clio; Diplectrona modesta; Glossosoma intermedium; Hesperophylax designatus; Lepidostoma liba; Pheromermis pachysoma; Pheromermis vesparum; prevalence and intensity of infection